2021
DOI: 10.1093/advances/nmaa145
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Fiber, Fruit, and Vegetable Consumption with Risk of Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: No previous investigation has summarized findings from prospective cohort studies on the association between dietary intake of fiber, fruit, and vegetables and risk of inflammatory bowel disease (IBD). Dietary fiber and its major sources can influence the risk of IBD by modulation of the gut microbiota. This study summarizes findings from published cohort studies on the association between dietary fiber, fruit, and vegetable consumption and risk of IBD. Relevant articles published up to January 2019 were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 46 publications
2
54
0
1
Order By: Relevance
“…A more recent meta-analysis on four prospective studies [23,67,69,70] demonstrated a significant inverse association between fruit consumption with CD risk (Relative Risk (RR) 0.47; 95% CI: 0.38-0.58; I 2 = 32%) [71]. This association remained significant when analysed in subgroups in servings per day.…”
Section: • Mozzarella Cheesementioning
confidence: 97%
See 2 more Smart Citations
“…A more recent meta-analysis on four prospective studies [23,67,69,70] demonstrated a significant inverse association between fruit consumption with CD risk (Relative Risk (RR) 0.47; 95% CI: 0.38-0.58; I 2 = 32%) [71]. This association remained significant when analysed in subgroups in servings per day.…”
Section: • Mozzarella Cheesementioning
confidence: 97%
“…The earlier systematic review on fruit and UC development that also included casecontrol studies, reported that none of eight included studies in the systematic review showed significant results (OR range 0.42-2.9) [41]. In the later systematic review including the same four earlier mentioned studies, a pooled analysis demonstrated that fruit intake (g/day) was significantly associated with UC risk (RR 0.69; 95% CI: 0.55-0.86; I 2 = 87%) [71]. However, this association lost significance when it was performed in 1-3 servings/day in subgroups.…”
Section: • Mozzarella Cheesementioning
confidence: 97%
See 1 more Smart Citation
“…A smaller case-control study including men and women showed benefit in the subgroup of patient's with CD who were non-smokers [49]. A recently published systematic review with meta-analysis examined the association of dietary fibre, fruit and vegetable consumption with risk of IBD [58]. There was no significant association between dietary intake of fibre and risk of UC.…”
Section: Crohn's Disease Ulcerative Colitismentioning
confidence: 98%
“…When substrate is scarce, intestinal bacteria use the intestinal mucus as a nutrient, which leads to inflammation through close contact between bacteria and the epithelial layer [37]. Long-term intake of fibers from fruit has been shown to be protective against the development of CD, but not of UC [38][39][40][41][42].…”
Section: Fiber and Ibdmentioning
confidence: 99%